Two Mixed-Ligand Cu(II) Polymers: Treatment Activity on Acute Cerebral Infarction Combined with Alteplase - Wen-Ping Liu; Tao Xue; Yangchun Li; Ruoyu Cui (Journal of Chemistry)
With the reaction between Cu(NO3)2·3H2O and 4-(2′,3′-dicarboxylphenoxy) benzoic acid (H3L), a semirigid trichromatic acid ligand, in the presence of N-donor co-ligand 1,2-bis(4-pyridyl) ethylene (bpe), two novel mixed-ligand coordination polymers (CPs), i.e., [Cu(H2L)2(bpe)(H2O)2]bpe·(H2O)4 (1) and [Cu3(L)2(bpe)3(H2O)4]·(H2O)6 (2), have been created under different solvent systems. Furthermore, the biological activity of compounds was evaluated, and the related mechanism was explored as well. Firstly, the enzyme-linked immunosorbent assay (ELISA) was conducted to measure the content of coagulation factors in the serum after compound treatment. In addition to this, the real-time reverse transcription-polymerase chain reaction (RT-PCR) assay was conducted, and the inflammatory response in the brain was also determined.